Salivary calculus excision in the submandibular gland: case report - Custódio, Gustavo Paiva (2021)
Salivary calculi or sialoliths are calcified bodies that develop inside the salivary canal, through the accumulation of calcium salts around the ductal lumen, affecting the submandibular gland, although they also occur in the sublingual and parotid glands. These disorders are manifested in small sizes and can, in some cases, reach large proportions. Anatomically, the tortuous and ascending canal of the submandibular gland (Wharton's duct) and the quality of its thick mucoid secretion are intrinsic factors for the appearance of salivary calculus. These calculations can appear in any age group, being more common in young and middle-aged adults. The aim of this paper is to discuss the clinical case of exposed, symptomatic salivary calculus affecting the right side of Wharton's duct in a 56-year-old patient treated with simple surgical removal. Sialolithiasis can appear asymptomatic, but it can also show episodes of decreased salivary flow, pain and swelling of the affected gland with episodes of infection. The severity can vary depending on the degree of obstruction and the negative pressure produced inside the gland. Treatment may be conservative or surgical, taking into account the affected gland and the size of the stone. It was concluded that the most effective conduct in the management of the lesion is through surgical removal through intraoral access and these disorders are primary through clinical examination, and knowledge about the pathologies that involve the oral cavity is extremely important.